As contradições do espaço rural do município de Japaratuba/SE : da produção de commodities aos alimentos agroecológicos - Santos, Lucas Feitosa dos (2022)
Brazilian agriculture is highlighted by the agribusiness sector and by the ruralist caucus in the congress as a generator of profit and development for the national economy. Its exchange value is mainly related to the production of goods for the foreign market. From the 1960s onwards, with the development of agriculture based on the paradigm of the Green Revolution, encouraged by public policies and funding made available by the State, faster transformations occurred in rural areas, in addition to perpetuating the concentration of land, wealth and power. . As the monoculture of different products advances (sugarcane, soybeans, corn), the use of pesticides and genetically modified seeds increases and, on the other hand, the areas of food production for domestic supply are reduced. , accentuating the social and environmental problems in the countryside with the expansion of Agribusiness. In contrast to the conventionalconservative model of agricultural development, the paradigm of agroecological production based on sustainable agriculture that aims to grow healthy foods and without the use of pesticides, practiced by peasant family farmers and which emphasize the importance of Safety and Food sovereignty of the peoples by creating alternatives to the corporate agri-food system. This research is characterized as a qualitative approach and, for its development, references such as books, theses, dissertations and articles that address the studied theme were used. At the same time, information collection and field visits were carried out to rural communities, in which interviews were carried out with peasant family farmers. Secondary data collection was extracted from the 2006 and 2017 Agricultural Censuses and from the Municipal Agricultural Survey — PAM carried out by the Brazilian Institute of Geography and Statistics — IBGE. Thus, the general objective of this dissertation is to analyze the dynamics and contradictions of agroecological production implemented by farmers in the face of the advance of commodities in the municipality of Japaratuba/SE. The specific objectives are: to characterize the agroecological production practices developed by the farmers in relation to the sugar and alcohol agribusiness; identify the commercialization circuits of agroecological products; analyze how agroecological agriculture contributes to the autonomy and reproduction of farmers in the face of the commoditization of the territory; to evaluate the relationship between public policies and the implementation and development of agroecological practices in the municipality of Japaratuba. We seek, through the territory as a category of geographic analysis, to understand the multiple dimensions, the production of material and immaterial elements of social and economic reproduction of the social subjects studied. in opposition to the advance of the commoditization of their territories.